Human and Children’s Rights in the Context of Education and School Mediation - Spann, Martina; Torrego Seijo, Juan Carlos; Monge López, Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
There is common understanding among the member states of the UN on Human and Children’s Rights and that everyone has a right to life, liberty, and security of person. Children are entitled to special care. Social changes caused by migration or armed conflicts affect families and may have negative consequences on children’s welfare. Violent family structures are often transported into the schools. Evidence on school mediation and conflict resolution programs between peers seems to be a good method to teach children how to resolve conflicts peacefully. This paper also researches how such programs can contribute to a more conflict-free society.